Voice Recognition Systems for The Disabled Electorate: Critical Review on Architectures and Authentication Strategies - Olayemi Mikail Olaniyi; Jibril Abdullah Bala; Shefiu Ganiyu; Yunusa Simpa Abdulsalam; Chimdiebube Emmanuel Eke (Computer Engineering and Applications Journal, 2023)
An inevitable factor that makes the concept of electronic voting irresistible is the fact that it offers the possibility of exceeding the manual voting process in terms of convenience, widespread participation, and consideration for People Living with Disabilities. The underlying voting technology and ballot design can determine the credibility of election results, influence how voters felt about their ability to exercise their right to vote, and their willingness to accept the legitimacy of electoral results. However, the adoption of e-voting systems has unveiled a new set of problems such as security threats, trust, and reliability of voting systems and the electoral process itself. This paper presents a critical literature review on concepts, architectures, and existing authentication strategies in voice recognition systems for the e-voting system for the disabled electorate. Consequently, in this paper, an intelligent yet secure scheme for electronic voting systems specifically for people living with disabilities is presented.